How Digital Leadership Drives Innovation and Collaboration in Higher Education: The Mediating Role of Psychological Empowerment - Gunawan, Ahmad; Kusumah, Dadang Heri; Nurmalasari, Depi; Safira, Syiva; Manan, Irma Rohmatul (Equator Journal of Management and Entrepreneurship (EJME), 2026)
The digital transformation of higher education institutions (HEIs) has accelerated the adoption of hybrid academic work arrangements, fundamentally reshaping how innovation and collaboration are enacted. In this context, digital leadership has emerged as a critical capability for university leaders; however, empirical evidence explaining the psychological mechanisms through which digital leadership influences academic outcomes remains limited. This study investigates the role of psychological empowerment as a mediating mechanism in the relationship between digital leadership, innovation, and collaboration within hybrid work environments in HEIs. Using a quantitative research design, data were collected from academic staff working under hybrid arrangements across higher education institutions. The proposed model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that digital leadership has a significant positive effect on psychological empowerment, which in turn positively influences both innovation and collaboration. Moreover, digital leadership directly enhances innovation and collaboration, while psychological empowerment partially mediates these relationships. The results contribute to the digital leadership literature by elucidating the psychological processes that link leadership practices to innovation-related outcomes in higher education. From a practical perspective, the study highlights the importance of fostering psychologically empowering digital leadership to sustain innovation and collaboration in hybrid academic work settings. These findings offer actionable insights for university leaders navigating ongoing digital transformation.